hi,
b + g = 23 ------equation (1)
b = g - 3 ------equation (2)
you can substitute the equation of b into the 1st one to become:
(g - 3) + g = 23
so,
2g - 3 = 23
move the (-3) to the right side, it becomes positive.
2g = 26
so if 2g = 26,
--> g = 26 / 2 = 13
2007-01-10 18:24:04
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
u have 2 equations the first is b+g=23 & second is b=g-3. take the first equation b+g=3 & seperate like this b=23-g now put this value in second eq. and than g-3=23-g
g+g=23+3
2g=26
g=13
now put this value in b=g-3 u will get
b=13-3
b=10
it means there r 13 girls in the class
2007-01-11 02:43:40
·
answer #2
·
answered by uamir g 1
·
0⤊
0⤋
The Facts:
(1) b= boys, g=girls
(2)b+g=23
(3)b=g-3
We can then substitute (3) into (2) and we get:
g-3+g=23
Now by adding like terms we get:
g+g-3=23
2g-3=23
Now we want to isolate 2g so we add 3 to both sides of the equation and we get:
2g-3+3=23+3 this equals:
2g=26
Now to get g we divided by 2:
2g/2=26/2
g=13 There are 13 girls in Mr.Titelbaum's class.
2007-01-11 02:33:53
·
answer #3
·
answered by Albertan 6
·
0⤊
0⤋
Here,there are two variables b and g
We can establish their inter-relation in the following way
b+g=23
=. b=23-g
But in the second part of the problem it is given that b=g-3
Therefore 23-g=g-3
=>-g-g=-3-23
=>-2g=-26
Therefore g=-26/-2=13
The no of girls are,therfore=13
2007-01-11 02:31:22
·
answer #4
·
answered by alpha 7
·
0⤊
0⤋
b + g = 23
b = g - 3
This is a problem with two equations and two unknowns. Let's rearrange the second equation so that it's in the same form as the first equation.
b + g = 23
b - g = -3
To solve this, we use elimination. Add these two equations; notice you have a +g in the first equation and a -g in the second; they would promptly cancel each other out.
2b = 20
Now, solve for b.
b = 10
To solve for g, all you have to do is plug in b = 10 into any of the two equations.
Since b - g = -3, then
10 - g = -3, and
10 + 3 = g, so g = 13
There are 13 girls and 10 boys.
2007-01-11 02:26:45
·
answer #5
·
answered by Puggy 7
·
0⤊
0⤋
you say that b=g-3
so think of it this way, ANYTIME you see the letter b, you substitute it with g-3. because, you say that b=g-3, so those two things are identical. they are interchangeable. to solve the problem you want to get rid of one of the variables, so it's easy to solve. you know that b=g-3 so substitute it for b in in the equation. it will look like this: (g-3) + g = 23
2g-3=23
2g= 23+3
2g = 26 so then g=13
2007-01-11 02:50:08
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
13, dang it, I was a lil late... I considered the average number between the two and thought of the numbers close to mean, and it was of course girls at 13 and boys at 10, which are the only numbers that add up to 23 and have a difference of three between the boys and girls...
Variables give you clues in finding the unknown numbers...
2007-01-11 02:25:13
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋